Studi Analisis Dampak Lalu Lintas Pembangunan Jembatan Kembar Kota Parepare - Ashar Bakri; Muh. Nashir. T; Adnan Adnan (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The construction of the Parepare City Twin Bridges resulted in increasing vehicle volumes and the occurrence of traffic jams which resulted in obstruction of traffic flow or congestion. The aim of this research is to determine the existing conditions, performance of intersections and road sections and their handling. The type of research used is quantitative, with the data collection method carried out (survey) and the data analysis used is MKJI 1997. The results of this research show that the existing condition of the intersection and road sections in segment 1 is at level of service (LoS) B, segment 2 v/c ratio is at level of service (LoS) A, and segment 3 v/c ratio value is at level of service (LoS) A. The performance of intersections and roads in Segment 1, namely Jl. The peak hour for the Makassar-Parepare axis is 16.00-17.00 (afternoon) Monday, the traffic flow value (Qtot) is 1812.5 pcu/hour, the saturation degree (DS) value is 0.21. Segment 2 is Jl. Gen. M. Yusuf and Jl. Arung Mampi peak hours are 16.00-17.00 (afternoon) on Mondays. The traffic flow value (Qtot) is 262.7 pcu/hour, the degree of saturation (DS) value is 0.05. The handling is installing traffic signs; installation of warning lights or traffic lights.